What do elementary students know about science, scientists and how they do their work?. Issue 4 (4th March 2022) - Bartels, Selina; Lederman, Judith
ABSTRACT: Scientific literacy is the primary goal of elementary science education. Scientific literacy requires an overall understanding of what science is, and how and why scientific knowledge is developed. The normal assumption is that as students progress in school, they learn more. One would expect students to become more scientifically literate as they progress in school. There is very little empirical evidence, however, suggesting that students become more scientifically literate as they move through school. The purpose of this study was to see if elementary students' understandings of science, scientists and how scientists do their work differed throughout elementary school. The study draws on a sample of 338 students from 18 different classrooms situated in and around a large US city. This study assesses students' views of science and scientists as well as their understandings of aspects of scientific inquiry (SI) and the nature of science (NOS) that elementary students are able to understand. Overall findings illustrate students' understandings of science, scientists and how they do their work did not significantly change from grade one to grade five. This study can serve as a springboard for suggestions concerning scientific literacy research in the primary grades.